How to control vendor service to avoid fraud in insurance sector - Morais, F.; Pereira, L.; Dias, Á.; Gonçalves, R.; Lopes da Costa, R. (International Journal of Services and Operations Management, 2024)
The difficulty in controlling the quality of services provided by external providers, in the settlement of multi-risk claims, increases the risk of fraud and constitutes an obstacle for insurance companies. The methodology used seeks to understand the evolution of quality control of external providers; to identify the causes of the incapacity to implement adequate controls and the main impacts of this constraint; and to define the best solution to solve the problem and the benefits for the company. Although there is a greater concern, controls are still insufficient, which may create economic and financial losses, negatively impact customer satisfaction and weaken the company's image. The lack of sensitivity to fraud and the misuse of resources condition adequate quality control. Audits and the parameterisation and automation of controls offer greater robustness to the company, increase security with customers and control financial waste.